Quorum sensing and antibiotic resistance in polymicrobial infections - Sunny Cui; Esther Kim (Communicative & Integrative Biology)
Quorum sensing (QS) is a critical bacterial communication system regulating behaviors like biofilm formation, virulence, and antibiotic resistance. This review highlights QS’s role in polymicrobial infections, where bacterial species interactions enhance antibiotic resistance. We examine QS mechanisms, such as acyl-homoserine lactones (AHLs) in Gram-negative bacteria and autoinducing peptides (AIPs) in Gram-positive bacteria, and their impact on biofilm-associated antibiotic resistance. The challenges uniquely associated with polymicrobial infections, such as those found in cystic fibrosis lung infections, chronic wound infections, and medical device infections, are also summarized. Furthermore, we explore various laboratory models, including flow cells and dual-species culture models, used to study QS interactions in polymicrobial environments. The review also discusses promising quorum sensing inhibitors (QSIs), such as furanones and AHL analogs, which have demonstrated efficacy in reducing biofilm formation and virulence in laboratory and clinical studies. By addressing the interplay between QS and antibiotic resistance, this paper aims to advance therapeutic strategies that disrupt bacterial communication and improve antibiotic efficacy, ultimately mitigating the global challenge of antibiotic resistance in polymicrobial infections.